WARNA DAN EMOSI UNTUK MEDIA DESAIN INTERAKTIF: LITERATURE REVIEW - Nurmalita Zahra; Alvanov Zpalanzani Mansoor (Gorga : Jurnal Seni Rupa, 2024)
Color is considered in the application of emotion or psychological themed interactive design media. Previous research on color and emotion shows that color manipulates a person's emotions. This article discuss about association of color and emotion or psychology for reference to the use of color in interactive design media with psychological themes. This research method is a literature review with limitations related to emotions and psychology to find out what things need to be considered for deciding what colors can be used in research and designing psychology-based interactive design media.. The result of this research is a color can be associated with different emotions in different people. Things that affect the difference are religion, geography, language, culture, gender, age, duration of color exposure, and hue, saturation, and lightness (HSL), duration of color exposure, linguistics, culture, perception of the environment, gender, and age. This research can be used as a reference for researchers or designers in researching or creating interactive design media related to emotions and psychologyKeywords: Color, Emotion, Interactive Design MediaAbstrakWarna merupakan hal yang perlu diperhatikan dalam pengaplikasian pada media desain interaktif yang bertemakan emosi atau psikologi. Pada penelitian terdahulu tentang warna dan emosi menunjukan bahwa warna memanipulasi emosi seseorang. Artikel ini membahas tentang asosiasi warna dan emosi atau psikologi untuk acuan penggunaan warna dalam media desain interaktif bertemakan psikologi. Metode penelitian ini adalah literature review dengan batasan warna yang terkait dengan emosi dan psikologi untuk mengetahui hal apa saja yang perlu dipertimbangkan dalam memutuskan penggunaan warna apa saja yang dapat digunakan dalam penelitian maupun perancangan media desain interaktif berbasis psikologi. Hasil dari penelitian ini adalah sebuah warna dapat diasosiasikan dengan emosi yang berbeda pada orang yang berbeda. Hal yang mempengaruhi perbedaan tersebut adalah religi, geografis, bahasa, budaya, jenis kelamin, usia, durasi paparan warna, dan hue, saturation, dan lightness (HSL). Penelitian ini dapat digunakan sebagai acuan untuk peneliti atau desainer dalam meneliti atau menciptakan media desain interaktif yang berhubungan dengan emosi maupun psikologi.Kata Kunci: Warna, Emosi, Media Desain Interaktif. Authors:Nurmalita Zahra : Institut Teknologi BandungAlvanov Zpalanzani Mansoor : Institut Teknologi Bandung ReferencesDarmaprawira, S. (2002). Warna. Penerbit ITB.Dewi, F. N., & Rizky Mutiaz, I. (2023). Muatan Budaya China Dalam Desain Karakter Yun Jin Game Genshin Impact. Jurnal Seni Rupa, 12.Fugate, J. M. B., & Franco, C. L. (2019). What color is your anger? Assessing color-emotion pairings in english speakers. Frontiers in Psychology, 10(FEB). https://doi.org/10.3389/fpsyg.2019.00206Hanada, M. (2018). Correspondence analysis of color“emotion associations. Color Research and Application, 43(2). https://doi.org/10.1002/col.22171Jonauskaite, D., Dael, N., ChÃ¨vre, L., Althaus, B., Tremea, A., Charalambides, L., & Mohr, C. (2019). Pink for Girls, Red for Boys, and Blue for Both Genders: Colour Preferences in Children and Adults. Sex Roles, 80(9“10). https://doi.org/10.1007/s11199-018-0955-zJonauskaite, D., Parraga, C. A., Quiblier, M., & Mohr, C. (2020). Feeling Blue or Seeing Red? Similar Patterns of Emotion Associations With Colour Patches and Colour Terms. I-Perception, 11(1). https://doi.org/10.1177/2041669520902484Joosten, E., Van Lankveld, G., & Spronck, P. (2010). Colors and Emotion in Videogames. Proceedings on the 11th International Conference on Intelligent Games and Simulation GAME-ON 2010.Korkmaz, S., Ã–zer, Ã–., Kaya, Åž., Kazgan, A., & Atmaca, M. (2016). The correlation between color choices and impulsivity, anxiety and depression. European Journal of General Medicine, 13(3). https://doi.org/10.15197/ejgm.1592Liu, Y. (2022). The Colour-Emotion Association. Journal of Education, Humanities and Social Sciences, 5, 272“277. https://doi.org/10.54097/ehss.v5i.2912Livingstone, S. R., & Brown, A. R. (2005). Dynamic Response: Real-Time Adaptation for Music Emotion. Creativity & Cognition Studios Press, University of Technology, Sydney.Miswar, M., Rica, R., Yunis, M., & Rajudin, R. (2022). Studi Warna dan Gaya Pada Karya Yazid. Gorga¯: Jurnal Seni Rupa, 11.Pope, D. J., Butler, H., & Qualter, P. (2012). Emotional Understanding and Color-Emotion Associations in Children Aged 7-8 Years. Child Development Research, 2012, 1“9. https://doi.org/10.1155/2012/975670Purbasari, M., Luzar, L. C., & Farhia, Y. (2014). Analisis Asosiasi Kultural Atas Warna (Vol. 5, Issue 1).Zam, R., Dharsono, & Raharjo, T. (2022). Transformasi Estetik Seni Kriya; Kelahiran dan Kriya Masa Kini. Gorga¯: Jurnal Seni Rupa, 11(19).